Calorie Tracking: A Mobile Application for Tracking Eating Patterns and Intake - Gayatri, Nyoman Ayu Gita; Soegiarto, Juan Xavier; Sanjaya, Philips; Tanujaya, Vincent; Diporedjo, Nicholas; Kusnandar, Aaron Medhavi; Tjokro, Justin; Chandra, Yulyanty (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
A balanced regular calorie intake along with a good eating rules is an important factor to fullfill a healthy lifestyle and diet. Both are the main keys to preventing non-communicable diseases (NCDs) which are the largest contributors to world deaths. The effects produced through dietary regulation and calorie intake ideally will affect to the long term, so that consistency and adequate supporting media are needed. Judging from the time scale, action is needed since in, Early action is needed, especially for students who are in the transition period to maturity and independence. Technological developments in the digital era can be used to produce problem solutions ranging from fundamental aspects. Students themselves are familiar with the concept of the calorie tracker application (Craker) even though the majority have never used it. The purpose of this paper is to design the Craker application as a form of solution to regulate diet and calorie intake by applying the theory of human and computer interaction. The result of making this application is to monitor the number of calories consumed by knowing the number of calories in and out so that it is balanced according to the recommendations given based on the user’s profile, for the calorie tracker application we can divide it into three types of calorie tracker applications: web, mobile, and physical.